Amorphous nickel incorporated tin oxide thin film transistors. (11th August 2017) - Yang, Jianwen; Ren, Jinhua; Lin, Dong; Han, Yanbing; Qu, Mingyue; Pi, Shubin; Fu, Ruofan; Zhang, Qun
Abstract: Nickel as a dopant has been proposed to suppress excess carrier concentration in n-type tin oxide based thin film transistors (TFTs). The influences of Ni content on nickel doped tin oxide (TNO) thin films and their corresponding TFTs were investigated with experimental results showing that the TNO thin films are amorphous. Through the comparison of the transfer characteristic curves of the TNO TFTs with different Ni contents, it was observed that Ni doping is useful to improve the performance of SnO2 -based TFTs by suppressing the off-state current and shifting the threshold voltage to 0 V. The amorphous TNO TFT with 3.3 at.% Ni content shows optimum performance, with field effect mobility of 8.4 cm 2 V −1 s −1, saturation mobility of 6.8 cm 2 V −1 s −1, subthreshold swing value of 0.8 V/decade, and an on-off current ratio of 2.1 × 10 7 . Nevertheless, the bias stress stability of SnO2 -based TFTs deteriorate.